Case Report: Surgery combined with extracorporeal membraneoxygenation for acute type A aortic dissection complicated with acute myocardial infarction - Xia, Jianming; Qiu, Yan; Chang, Shuo; Feng, Ying; Zhang, Heng; Wang, Xiaoqi (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAcute myocardial infarction (AMI) is one of the most serious complications of acute type A aortic dissection (ATAAD) and markedly increases patient mortality. Simultaneous treatment strategies remain controversial. How to improve the treatment of these patients remains a critical challenge for cardiovascular surgeons.Case presentationAll three patients who experienced chest pain were admitted to emergency department of our hospital. The 12-lead electrocardiogram revealed ST-segment depression, myocardial enzyme levels were significantly elevated. Emergency physicians diagnosed ATAAD with AMI, and emergency surgery was planned in collaboration with the cardiovascular surgery team. One-stage surgery for coronary revascularization and central aortic repair were performed, extracorporeal membrane oxygenation (ECMO) was implanted, ECMO was discontinued when hemodynamics stabilized. The patient ultimately recovered well and was discharged.ConclusionFor ATAAD combined with right ventricular AMI, one-stage surgery for coronary revascularization and central aortic repair, supported by ECMO as bridge, can be life-saving treatment strategy, the prognosis for all three patients was excellent.